Study on the different methods of capturing CO2 and applications of abnormal glow discharge - Navas-Ciendúa, Manuel Alejandro; Sarmiento, Armando; Alvarez, Brenda (Uptc, 2022)
In recent years there have been great changes in the environment. Large industries generate pollution in the form of carbon dioxide ―CO2―. For this reason, research has focused on CO2 capture processes with the use of different techniques such as the plasma system in dielectric barrier discharge configuration and the integration of calcium cycle technologies, among others. Due to this, the objective of this document is to review the abnormal glow discharge method and give an overview of CO2 capture methods and technologies.